Effects of Guimaras oil spill on the quality of some aquatic organisms - Espino, Marinelle Salinas (Miagao, Iloilo University of the Philippines in the Visayas, 2007)
An investigation of the effects of petroleum-related compounds from the recent oil spill near the province of Guimaras on the quality of some aquatic organisms was conducted. Three samplings of different species of fish, namely Sardinella sp., sardines or "lupoy" (a pelagic species), nemipterus sp. Threadfin bream or "bisugo" (a demersal species), and chanos chanos, milkfish or "banagus" (an aquaculture species), and a managrove species of clam (Anadara sp.; arc shell; "litob") were conducted in some oil spill affected areas in the southwestern part of Guimaras to determine the extent of contamination/tainting in these species. Samples were monitored in terms of changes in the degree of tainting, the effect of petroleum contaminats on proximate composition, and the changes in the concentration of grease and oil present in the muscle tissue of the sampled species. Tainting was established using an objective sensory evaluation scheme that employed semi-trained, experiences panellists. The proximate composition of the samples was assessed in terms of their moisture, ash, crude protein and lipid contents. The concentration of grease and oil in the samples was quantified using the EPA method 9071B for the analyses of Hexane Extractable Material (HEM). Results of the study revealed that the degree of tainting in fish and shellfish was relatively higher on the first day of sampling (about 71 to 86 days after the oil spill incidence), but decrease to sensory score of o("no detectable petroleum like odor/flavour") on the last day of sampling (about 86to 96 days after the oil spill incidence). Moreover. The study showed that exposure of fish and shellfish to petroleum-related compounds has no effect on the proximate composition of the sampled species. In addition, there appears to be a direct relationship between the value of Hexane Extractable Materials (HEM) and the degree of tainting, but only in the shellfish Anadara sp. No significant correlation exists between the sensory scores for the finfish species and that of the HEM values obtained from these species. This study also showed that the extent of tainting in fish and shellfish is partly a function of the habitat of the species, the inherent characteristics of these species, and the degree and duration of exposure to petroleum contaminants. Further studies on long term effects of oil spill on exposed aquatic organisms should be conducted to verify if the exposure of fish and shellfish to petroleum related compounds after an oil spill incidence would lead to deposition/integration of aromatic compounds into the tissues of organisms with slow or inefficient metabolism (e.g. shellfishes). In addition, due to the difficulties encountered during the sampling days in this study, it is recommended that a cost-effective plan for sampling, monitoring and analysis of aquatic organisms that have been exposed to petroleum related compounds following an oil spill incidence be properly designed in a future study.
Thesis (Undergraduate, Bachelor of Science in Fisheries) Institute of Fish Processing Technology, College of Fisheries and Ocean Sciences, University of the Philippines Visayas. 2007..
Keywords: Oil spill; Aquatic organism; Quality